Chapter A Quantitative Analysis of Theonyms and Panthea in the Hittite Cult Inventories - Cammarosano, Michele (Studia Asiana, 2023)
The riches of the Hittite tablet collections are justly famous for the great mass of information they provide about deities, cult, and religious beliefs all over the Kingdom of Hattusa. The sheer amount of available texts and the fragmented state of many of them pose nontrivial problems for any systematic study of the Hittite religion. Expanding on the digital edition of the so-called cult inventories (CTH 526-530, ca. 450 fragments) and exploiting the potential of the related database, this paper provides for the first time a quantitative analysis of the panthea of local towns in the core area of the kingdom in the Late Empire period. The study is organized in two parts. Part One sets out the methodological basis for the analysis by examining the target corpus in terms of internal consistency, discussing the appropriateness of a distinction between "state" vs. "nonstate" cults both within the perspective of the current discourse on Hittite religion and specifically with regard to its consequences for the proposed analysis, and laying out the analytical principles used in the extraction of the relevant information. Part Two presents selected sets of data, explores ways to interpret and combine them, and investigates their significance for the study of local panthea in the Late Empire. The results are twofold. On the one hand, an innovative picture of the panthea under discussion is obtained, with substantial implications for our understanding of a number of deities, their relationship to each other, and their role within the religious life of provincial communities. On the other hand, the critical scrutiny of the nature and specific traits of the data sample highlights methodological pitfalls in a purely quantitative analysis of Hittite religious texts, and proposes correctives for mitigating their impact, thereby providing a significant case study for future research.